Un/limited - Yanowitz, Zachary, author; Beachy-Quick, Dan, advisor; Steensen, Sasha, committee member; Lehene, Marius, committee member (Colorado State University. Libraries, 2018)
UN/LIMITED is a collection of poems divided into three primary sections, moving from a group with multiple versions of "I" through to one long poem with multiple versions of "You." Focused primarily around themes of grief, emotional instability, and maturity, the book attempts to parse what it means to be a poet and an empathetic human being in a contemporary world—and a single body—thrumming with limitless potential and possibility.
Keywords: poetry